Green synthesis of mesoporous ZnFe2O4/C composite microspheres as superior anode materials for lithium-ion batteries - Yao, L.; Hou, X.; Hu, S.; Wang, J.; Li, M.; Su, Chao; Tade, Moses; Shao, Zongping; Liu, X. (Elsevier SA, 2014)
The commercialized LIBs employing graphite as anodes currently suffer a series of problems from the safety, theoretical capacity (372 mAh g-1) and rate capability. Herein, self-assembly mesoporous Zn ferrite (ZnFe2O4) microsphere embedded into carbon network has been synthesized by a facile method in the presence of citric acid. The Zn ferrites as an anode material with novel structure demonstrate superior electrochemical performance, with enhanced specific reversible capacity (~1100 mAh g-1 at the specific current of 0.05 A g-1 after 100 cycles), excellent rate capability (more than 500 mAh g-1 even at the specific current of 1.1 A g-1) and good cycleability with little fading (~97.6% after 100 cycles). The excellent cycling performance is associated with the loose Zn ferrite microsphere with numerous mesopores embedded into the carbon network, which can accommodate the severe mechanism strains and provides good electrical contact and conductivity. The superior electrochemical performance may facilitate ZnFe2O4 to be a promising alternative anode in lithium ion battery.